Program Karang Taruna dalam Pengembangan Nutripreneur Masa Depan - Wahyuningtyas, Widayani; Riadhasilmi, Nazzala; Rezky, Nur Sofia; Butar, Yelvi Firstiana Butar (Civiliza Publishing, 2024)
In the year 2045, Indonesia has an ambitious vision to become the